The Transformation of Campaign Media and Its Impact in the Binjai City Regional Election - Indra Fauzan; Ira Rizka Aisyah Lubis; Riky Ovaliansyah Harahap; Dea Amanda Sembiring (JUSS (Jurnal Sosial Soedirman), 2026)
Abstrak: The transformation of campaign media in the digital era has led to the assumption that social media is the dominant factor in shaping voter preferences. Based on this premise, this study aims to analyze the transformation of campaign media and its influence on voter preferences in the 2024 Binjai mayoral election. This research employs a political communication approach using a quantitative survey method across various campaign media channels, including social media, mass media, print media, and other platforms. The findings indicate that conventional media, such as billboards and banners, continue to have a significant influence despite the increasing use of social media. Campaign media operate in a complementary manner in shaping candidate images, indicating that the effectiveness of campaign strategies depends on cross-platform synergy.